2016
DOI: 10.1021/acs.biochem.5b01166
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of a Histone Tail by a DNA Lesion in a Nucleosome Suggests the Lesion Impacts Epigenetic Marking: A Molecular Dynamics Study

Abstract: Errors in epigenetic markings are associated with human diseases, including cancer. We have used molecular dynamics simulations of a nucleosome containing the 10S (+)-trans-anti-B[a]P-N2-dG lesion, derived from the environmental pro-carcinogen benzo[a]pyrene, to elucidate the impact of the lesion on the structure and dynamics of a nearby histone N-terminal tail. Our results show that a lysine-containing part of this H2B tail that is subject to post-translational modification is engulfed by the enlarged DNA min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…A similar three-component system has recently been modeled with the (+)- trans - anti -BP- N 2 -dGuo DNA adduct and the residues of a histone tail. 39 …”
Section: Discussionmentioning
confidence: 99%
“…A similar three-component system has recently been modeled with the (+)- trans - anti -BP- N 2 -dGuo DNA adduct and the residues of a histone tail. 39 …”
Section: Discussionmentioning
confidence: 99%
“…52 Even the presence of a bulky lesion in the DNA near the H2B tail has been simulated to change the tail conformation. 53 Removal of εA at site 96, near the H2B and H4 tails (Figure 5), is significantly inhibited by H3 tail removal but not H2B tail removal. Surprisingly, the shift of the HRF maximum in this region to position 97, making it more OUT, for the gH3 NCP does not enhance εA excision.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Histone tails are essential for formation of nucleosomal arrays through extensive intra- and internucleosomal contacts . Even the presence of a bulky lesion in the DNA near the H2B tail has been simulated to change the tail conformation . Removal of εA at site 96, near the H2B and H4 tails (Figure ), is significantly inhibited by H3 tail removal but not H2B tail removal.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that this base-displaced/intercalated adduct weakens local histone-DNA interactions and causes severe local DNA distortions [41]. Additionally, we have studied a stereoisomerically different B[ a ]P-derived DNA adduct, the 10 S (+)- trans -B[ a ]P- N 2 -dG adduct which resides in the B-DNA minor groove [42]; it was placed at super-helical location (SHL) ~ 3 in the nucleosome environment [43, 44]. In this case, a single nearby histone H2B tail was stably engulfed by the B[ a ]P ring system [43], and upon lysine acetylation of the tail, tail-B[ a ]P interactions were destabilized [44].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have studied a stereoisomerically different B[ a ]P-derived DNA adduct, the 10 S (+)- trans -B[ a ]P- N 2 -dG adduct which resides in the B-DNA minor groove [42]; it was placed at super-helical location (SHL) ~ 3 in the nucleosome environment [43, 44]. In this case, a single nearby histone H2B tail was stably engulfed by the B[ a ]P ring system [43], and upon lysine acetylation of the tail, tail-B[ a ]P interactions were destabilized [44]. To further investigate the interactions of histone tails with DNA lesions, here we investigated the well-repaired cis -B[ a ]P-dG DNA adduct [3335] bracketed by the H3 and H4 tails in a nucleosome with all tails present (PDB [40] ID: 1KX5 [45]), and considered the H4 tail in unacetylated and acetylated states.…”
Section: Introductionmentioning
confidence: 99%